The Treatment of Ethiopian Consumer Cooperative Societies under the Ethiopian Income Tax and Value Added Tax Regime: Law and Practice - Silesh, Gizachew; Gebreselassie, Teklemuz; Redae, Dawit (Bahir Dar University Journal of Law, 2023)
The economic and social contribution of Cooperative Societies is immense in Ethiopia. In recognition of this, Federal Co-operative Society Proclamation No_985/2016 exempt them from income tax with restrictions on their transaction. Yet, they are obliged to pay all other direct and indirect taxes including VAT. There has been a rampant complaint in many parts of the country over the transactions of these institutions and their income & VAT treatment. The article aims at examining the magnitude and manifestations of the problem of Consumer Cooperative Societies taxation in Addis Ababa city and other three regional states (Amhara, SNNP, and Oromiya). To attain this, a qualitative research approach is employed in the course of which pertinent legislations, key informant interviews, and literature have been explored, analyzed and synthesized. The FDRE Constitution, Ethiopian Cooperative Laws, and other legislations are used as primary sources of data. Key informant interview has also been conducted with authorities in Federal and city administration Cooperative Agencies and Revenue Authorities. Additionally, books, articles, journals, and other relevant materials on the subject are examined as secondary data sources. Finally, the study concludes that the Consumer Cooperatives in the study area are transacting outside members without taking into consideration the unique feature of â€˜serving only membersâ€™ and this income is treated as the income from Cooperative members; and there is no uniform system on levying and collecting of VAT., Therefore, Cooperative Agencies and Revenue Authorities of the country should exercise their mandate of regulating Cooperative transactions and taxation.